Kajian Tentang Penelantaran Ekonomi sebagai Kekerasan dalam Rumah Tangga - Kodai, D. Aisa (Universitas Gorontalo, 2018)
Economic neglect is one form of domestic violence that has occurred even in small intensities. Behavior or acts of violence in the household as a social fact is not a new case in Indonesian society. Domestic violence (KDRT) is a social fact that is universal because it can happen in a household. Abandonment of households is one of the prohibitions that includes the scope of domestic violence as contained in Article 5 of the Law on the Elimination of Domestic Violence (UUPKDRT).